CD146 promotes resistance of NSCLC brain metastases to pemetrexed via the NF-κB signaling pathway - Qu, Hao; Fang, Yan; Zhang, Feng; Liu, Wenwen; Xia, Shengkai; Duan, Wenzhe; Zou, Kun (Frontiers in Pharmacology, 2025)
IntroductionPemetrexed is a first line drug for brain metastases from lung cancer, either as monotherapy or combined with other drugs. The frequent occurrence of initial and acquired resistance to pemetrexed results in limited treatment effectiveness in brain metastases. CD146 was recently found to play important roles in chemoresistance and tumor progression. However, the underlying mechanisms of CD146’s effects in pemetrexed resistance remain undefined.Method and resultsSensitivity to pemetrexed was assessed with a preclinical brain metastasis (BM) model based on lung adenocarcinoma PC9 cells. The role and mechanism of CD146 in pemetrexed resistance in non-small cell lung cancer (NSCLC) brain metastasis were explored in vitro and in vivo. A subpopulation of brain metastatic cells derived from progenitor PC9 cells (PC9-BrMS) was significantly resistant to pemetrexed. CD146 levels were significantly increased in pemetrexed resistant brain metastases, while CD146 inhibition suppressed pemetrexed resistance in BM cells. Mechanistically, CD146 mediated pemetrexed resistance in brain metastatic cells by promoting DNA damage repair, maintaining normal cell cycle progression, and regulating the NF-KB pathway to counter apoptosis, and these effects was based on increased DNA damage, cell cycle arrest, and occurrence of apoptosis after CD146 inhibition as well as the reemergence of pemetrexed resistance after CD146 restoration.DiscussionIn summary, this study revealed that the resistance of NSCLC brain metastatic cells to PEM was dependent on CD146.Thus CD146 might be targeted in clinic to overcome pemetrexed resistance in brain metastases from NSCLC.